2010
DOI: 10.1152/japplphysiol.00490.2009
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone represses ubiquitin ligases atrogin-1 and Murf-1 expression in an androgen-sensitive rat skeletal muscle in vivo

Abstract: Skeletal muscle atrophy induced by denervation and metabolic diseases has been associated with increased ubiquitin ligase expression. In the present study, we evaluate the influence of androgens on muscle ubiquitin ligases atrogin-1/MAFbx/FBXO32 and Murf-1/Trim63 expression and its correlation with maintenance of muscle mass by using the testosterone-dependent fast-twitch levator ani muscle (LA) from normal or castrated adult male Wistar rats. Gene expression was determined by qRT-PCR and/or immunoblotting. Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 64 publications
2
27
0
1
Order By: Relevance
“…Testosterone is known to suppress the ubiquitin ligase‐mediated atrophy pathway to preserve muscle mass 34, 37, 38, 39. Here again, our results support the idea that urolithin B mimics the effects of testosterone as it decreased the mRNA of the muscle‐specific ligases MuRF1 and MAFbx and the level of ubiquitinated proteins both in vitro and in denervated muscles.…”
Section: Discussionsupporting
confidence: 84%
“…Testosterone is known to suppress the ubiquitin ligase‐mediated atrophy pathway to preserve muscle mass 34, 37, 38, 39. Here again, our results support the idea that urolithin B mimics the effects of testosterone as it decreased the mRNA of the muscle‐specific ligases MuRF1 and MAFbx and the level of ubiquitinated proteins both in vitro and in denervated muscles.…”
Section: Discussionsupporting
confidence: 84%
“…In a recent study done by Pires-Oliveira et al (2010), Fbxo32 expression was high in rat m. levator ani over a week after castration, and this increase could be reversed by treatment with testosterone. Interestingly, in another recent study done by Rogers et al (2010), mice showed decreased expression of Fbxo32 12 weeks after castration similar to what was observed in our study.…”
Section: Regulated Genes In Common For Dht and Ementioning
confidence: 87%
“…Although we did not see any changes in Fbxo32 expression in vivo , expression of Fbxo32 was repressed by DHT in myoblasts in vitro . Other orchidectomy studies have shown upregulation of Fbxo32 expression in muscle,1351 with increased muscle protein degradation during atrophy,52 while androgen treatment increases muscle protein synthesis 53. Therefore, it is possible that androgen withdrawal-dependent atrophy occurs in part via the same myogenin-dependent ubiquitin ligase pathways activated in neurogenic atrophy, due to the loss of myogenin and Fbxo32 repression by the AR.…”
Section: Discussionmentioning
confidence: 99%